Kesalahan siswa SMP dalam memecahkan masalah soal tipe high order thinking skill (HOTS) ditinjau dari gaya belajar visual (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
High Order Thinking Skills (HOTS) is students' mathematical ability that connects their knowledge and experience to solve a problem, critically, creatively, and powerfully. Students' errors in solving HOTS type problems can be seen using the error criteria according to Watson with eight error indicators. Visual learning style is one aspect that influences students in solving problems. This type of research is descriptive qualitative. Selection of subjects using a purposive sampling technique and selected one subject with a visual learning style. The result of this research is that the subject with visual learning style made as many as four errors from a total of eight error indicators that have been used in this study.
Keywords: high order thinking skill (HOTS); error analysis; learning style